Effects of participation in a sports exercise programme on movement competencies of mentally retarded children - Kutlu, M; Sezer, YS; Kamanli, A; Karacabey, K; Ozmerdivanli, R (Cambridge Univ Press, 2000)
[Abstract Not Available]